2019
DOI: 10.14744/dajpns.2019.00006
|View full text |Cite
|
Sign up to set email alerts
|

The association between hope, anxiety, depression, coping strategies and perceived social support in patients with chronic kidney disease

Abstract: Objective: Patients with chronic kidney disease (CKD) may experience psychiatric problems while having to cope with the various characteristics of the disease. Identifying the level of hope, coping strategies, and perceived social support may provide valuable information to improve treatment plans and the response to treatment. This study aimed to evaluate the association between hope, anxiety, depression, coping strategies, and perceived social support in patients with CKD.Method: A total of 65 grade 3 or 4 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Motivators of treatment regimen adherence are predominantly family and system related in people with CKD (Chironda & Bhengu, 2018). Yucens et al (2018) showed that, as a strategy for reducing depression in patients with grade 3 or 4 CKD, multidisciplinary psychological counseling to instill hope and provide social support will facilitate treatment compliance.…”
Section: Discussionmentioning
confidence: 99%
“…Motivators of treatment regimen adherence are predominantly family and system related in people with CKD (Chironda & Bhengu, 2018). Yucens et al (2018) showed that, as a strategy for reducing depression in patients with grade 3 or 4 CKD, multidisciplinary psychological counseling to instill hope and provide social support will facilitate treatment compliance.…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between hope and social support has been demonstrated by numerous scholars—namely, Alshraifeen et al, Lin et al, and Yucens et al [ 16 18 ]. When people face life-threatening diseases or require long-term treatment, hope and social support can serve as buffer factors against physiological or psychological distress and coping and adjustment strategies.…”
Section: Introductionmentioning
confidence: 99%
“…When people face life-threatening diseases or require long-term treatment, hope and social support can serve as buffer factors against physiological or psychological distress and coping and adjustment strategies. Patients with good levels of hope and social support are more capable of resisting the stresses and effects of disease and treatment than patients without them; moreover, they have more faith in their treatment [ 16 , 18 ]. The findings reflect that hope, social support, and decisional conflict play crucial roles in how patients with ESRD cope with stressful events.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased ability for emptying the bladder completely thus increasing the risk of infection and obstruction and decreased fluid intake is a risk factor for kidney damage [12]. Results of research [13] also showed that the average age of respondents with chronic renal failure is 48 years old. Supported also by the results of research [14] showed that most respondents have a range of 35 to 65 years of age.…”
Section: Resultsmentioning
confidence: 99%